The development of the simulated transactions doctrine as means of combating impermissible tax avoidance - Griffin, Nicholas (Department of Commercial Law, 2021)
Tax avoidance may be an inevitable consequence of taxation; however, it remains a great drain on the fiscus. There are many ways in which the Commissioner may attack avoidance arrangements in order to lessen the drain on the fiscus. One manner in which the Commissioner may attack avoidance arrangements is through the doctrine of simulated transactions. Given that the simulated transactions doctrine is ordinarily a contract law doctrine and not strictly speaking a tax law mechanism one might wonder how this area of law might develop into an antiavoidance mechanism. This contribution sought to understand how the doctrine may develop as an anti-avoidance mechanism through an analysis of the development of the case law in regards to the development of the doctrine in order to ascertain how it has developed into a common-law anti-avoidance rule. In this regard selected cases were discussed which highlighted firstly the genesis of the simulated transactions doctrine in our law (Chapter 2) and selected cases were discussed that highlighted the simulated transactions doctrine's development and use as an anti-avoidance mechanism (Chapter 3) and finally the courts acceptance and treatment of this development and how this development was discussed in the literature was also discussed (Chapter 4) It was concluded that whilst the doctrine can be developed quite extensively as an anti-avoidance mechanism the courts are unlikely to develop same into a broad common-law General Anti-Avoidance Rule.